ISLAMISASI ILMU DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Sudarto Sudarto (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Islamization of Science is a necessity for the world of Islamic education today. Western civilization with its worldview has hegemony in almost all lines of the academic world. As a result, standards, policies, and concepts of science are more determined by Western perspectives than Islamic perspectives. This issue becomes an increasingly important issue for immediate response because the effects of secularization transplanted into science in the Islamic world have led to the confusion of the concept of science. This research was conducted at Sultan Agung Islamic University (UNISSULA) Semarang. Which aims to describe the concept and application of Islamic culture in terms of the perspective of Islamization of science. This study uses a qualitative research method using an evaluation approach as the analysis knife. Primary data and data sources were obtained from the head of the foundation, the Chancellor, the Vice Chancellor of three fields of curriculum and student affairs, initiators of Islamic Culture, leaders, lecturers, administrative staff, students, and UNISSULA alumni. The secondary data sources are from reading sources from libraries or various other sources that are considered relevant and supportive in providing research data. Thus the Islamization of contemporary science is a necessity that cannot be negotiable in the development of Islamic education.